2007
DOI: 10.1590/s1415-47572007000300003
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death 1 gene (PDCD1) polymorphism and pemphigus foliaceus (fogo selvagem) disease susceptibility

Abstract: Pemphigus foliaceus, also known as fogo selvagem, is an autoimmune disease of the epidermis characterized by superficial blisters and antibodies against desmoglein 1. It is a multifactorial disease and genetic susceptibility is oligogenic or polygenic. Considering the crucial function of the programmed cell death 1 molecule (PD-1) in the immune response, the aim of this study was to verify if variants of the PDCD1 gene influence susceptibility and resistance to pemphigus foliaceus, in a case -control disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…The first and strongest genetic associations ever reported were with the HLA class II genes encoding the beta chain of the HLA-DR and HLA-DQ molecules 5,6 . Polymorphisms in other proteincoding genes have been found associated with EPF [7][8][9][10][11][12][13][14] . A recent study showed that a 3' untranslated region polymorphism is associated with susceptibility to EPF by affecting a microRNA (miRNA) binding site 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The first and strongest genetic associations ever reported were with the HLA class II genes encoding the beta chain of the HLA-DR and HLA-DQ molecules 5,6 . Polymorphisms in other proteincoding genes have been found associated with EPF [7][8][9][10][11][12][13][14] . A recent study showed that a 3' untranslated region polymorphism is associated with susceptibility to EPF by affecting a microRNA (miRNA) binding site 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the strongest associations were found with HLA class II genes [15,16] and with CD40L [17]. Associations were also seen with IL6, IL4, IL10, PDCD1, CD40 and BLYS [17][18][19], but not with TNF, LTA, DSG1, BAX, TP53, and CD19 polymorphisms [17,20 -22]. Epistasis has been demonstrated between CD40 and BLYS, CD40L, and BLYS, and between DSG1 and HLA class II genes [17,23].…”
Section: Introductionmentioning
confidence: 99%
“…The rs10204525 may influence binding of microRNA and transcription factors, altering the expression of PD-1. Its major allele A was over-represented among the patients of predominantly European ancestry, but not in the Afro-Brazilian sample (Braun-Prado and Petzl-Erler, 2007).…”
Section: The B Lymphocyte Co-stimulators Cd40 Cd40lg Baff and Cd19mentioning
confidence: 78%